TINGKAT KEMATANGAN GONAD, FAKTOR KONDISI, DAN HUBUNGAN PANJANG-BERATIKAN TAJUK (Aphareus rutilans Cuvier, 1830) DI PERAIRAN LAUT DALAM PALABUHAN RATU, JAWA BARAT [The stage of gonad maturity, ponderal index, and Iength-weight relationship of Aphareus rutilans in Palabuhan ratu deep sea, West Java] - Frensly Damianus Hukom; Dewi Ratih Purnama; M F Rahardjo (Jurnal Iktiologi Indonesia, 2006)
The research was conducted in order to investigate condition factor, length-weight relationship, and reproductive aspect of Aphareus rutilans in Palabuhanratu Sea, Sukabumi, West Java from June 2005 to February 2006. Sample fish was captured by hand line. A total of 151 individuals were taken. The fish samples ranged from 245-830 mm in length. Length-weight relationship showed that fish had negative allometric growth type. Condition factor of male and female varied from 0.88 - 1.13 and 0.89 - 1.19 consecutively. Chi-Square test showed that sex ratio was unbalance. The stage of gonad maturity was found I, II, and IV for males and I - II for females.